Restoran Bisnis Berbasis Standar Kompetensi - Endang Darwin Durachim; Faizal Hamzah (LPPM Universitas Bina Sarana Informatika, 2017)
Restaurant Business base on competency is something important point to be presented on the activities of management Hotel or Restaurant, the reason is those thing will up-grade the Restaurant Business much better then before. Especially on the situation and condition of the business right now the competition getting so tight. So causing of those case we have to provide as well as possible , how to make the Competency Standard Attitudes, Skills and Knowledge are being presented on Restaurant Business. Actually the Competency Standard have three dominant factors indeed such as: All of dominant factors must be done in perfect condition or excellent Presentation , why the Competency Standard must be done in perfect condition ? because if the staff who In-Charge in the operation of the restaurant business, they are doing something Excellence Attitudes, Excellence Skills and Excellence Knowledge, so the whole of activities will be running well according to the necessarily of the restaurant business operation . In order to obtained an optimal result in the operation of the Restaurant Business is excellence of the presentation of the competency standard was carry out by Management and Staff. The basic purpose to obtained an optimal result was presented by Competency Standard , it will make all the guests / customers are satisfied, and automatically the productiveness / benefit or profit will come over directly to the management. Competency Standard is a statement of three interrelated components of Skills, Knowledge,and attitudes needed to carry out a particular tasks effectively in Industry. These are benchmarks made by Industry that are to be used to establish level of effective performance . They provide a framework to suit the needs of all the stockholder (Industry, Government , Training Provider, Trainees), regardless of location size. Key Factors: Restaurant Business Base on Competency , Socialization and Implementation of Competency Standard, Hierarchy of positions of Competency Standard in Tourism & Hospitality Industry,Realization powerful of strategy restaurant business base on competency standard .